The Importance of Lender-borrower Relationships to the Availability of Small and Micro Credit: Case Study on Indonesian Kredit Usaha Rakyat Loans - Suryani, Embun (International Journal of Economics and Financial Issues, 2018)
This study aims to examine how the relationships between a borrower and his potential lender affect the decisions of potential lender whether or not to provide or extend funds to the borrower. The author explores the available literature and original fieldwork to create a framework to capture this relationship. The study employs descriptive qualitative data to analyze and examine the research questions. The result shows that borrowers who build their commercial transactions with their lender on intensive relationships are more likely to receive and extend loans. The relationship effects arise because it motivates both lender and borrower to share private resources and facilitate access to loan opportunities, but does not influence the price of loans. To sum up, the lender-borrower relationships are valuable and seem to operate through quantities, trust and the length of these relationships. Furthermore, these relationships are more appropriate to be implemented for small and micro-lending. Keywords: lender-borrower relationship; asymmetric information; small and micro business; credit availability; price of loans. JEL Classifications: G21, O16, R51